Deep-fat frying process induces nutritional composition diversity of fried products assessed by SAIN/LIM scores. (March 2015) - Bassama, Joseph; Achir, Nawel; Trystram, Gilles; Collignan, Antoine; Bohuon, Philippe
Highlights: SAIN/LIM scores calculated from literature and experimental data for fried plantain products. Deep-fat frying options tested: oil type, product thickness, frying temperature, number of baths. Different profiles of fried products depending mostly on the oil type and the final oil content. Other methods proposed to calculated nutritional scores for processed products. Abstract: This paper analyzes the impact of deep-fat frying options on the nutritional profile of fried plantain-based products by using the SAIN, LIM system. 23 nutrients and 4 disqualifying compound including acrylamide were used to calculate SAIN and LIM scores. Experimental data for heat, mass transfers and reactions modeling were from previous studies. The options of the frying were oil type, micronutrient-enrichment or not, thickness of final product, frying temperature and number of baths. Frying turned plantain from neutral food to positive or negative categories as a function of process variables. The most impacting parameters were the oil type (SAIN and LIM scores of crisps varied by 6.5 and 7.5-fold respectively) and product thickness assimilated with the final oil content (LIM scores increased by 5-fold from 6% to 33% final fat content). Acrylamide increased LIM scores by 2 to 11-fold in crisps while the use of oils enriched with β-carotene impacted the SAIN scores by 10–20%. The best trade off process time/nutritional score was obtained for thick products (fat content <25%) fried in sunflower oil in non-isothermal conditions. The use of geometrical mean to calculate SAIN scores enabled a more sensitive evaluation of the effect of number of bath.